PERAN GCG DALAM MENGURANGI FINANCIAL DISTRESS: Dampak Penjualan dan Struktur Modal - Anandya Zalva Yunnafisah; Muhadjir Anwar; Fani Khoirotunnisa (Journal Publicuho, 2024)
This study examines how sales growth and capital structure affect financial hardship and finds that sound corporate governance acts as a mitigating factor. The research population includes companies in the transportation, utilities, and infrastructure sectors listed on the IDX during the 2018–2019 period. The sample was selected using purposive sampling, with 28 companies analyzed from 2018 to 2023, resulting in a total of 168 data points. Moderated Regression Analysis (MRA) utilizing SPSS 25 was used for the analysis. The results show that while capital structure has a beneficial influence on financial hardship, sales growth has a negative effect. Furthermore, good corporate governance strengthens the relationship between sales growth, capital structure, and financial distress.